Realistic Human Motion Preservation-Imitation Development on Robot with Kinect - Abdul Muis; Wisnu Indrajit (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
At most, motion generation on robot is usually done through complex computation in off-line mode and straightforward method. In straightforward method, the operator drives robot to certain pose either with moving manipulator tool-tip with hand or remotely. Once the desired pose achieved, the current pose is saved to memory. However, these methods are time consuming. An easy and quick approach is by imitating an object motion to robot with sensing devices. There have been numerous efforts for motion imitation either by using position sensitive detector (PSD) or by using stereo camera. However, a calibrated pre-condition should be done initially, which is not possible for natural movement. Here, this paper proposed motion preservation by capturing human motion naturally through Kinect and then reproduced human motion on humanoid robot simultaneously. In addition, the motions are also preserved in database for later used on robot motion generation and teaching as well. Furthermore, the robot motions are developed to run smoothly and close to human eye ability. The proposed method has been validated in experimental results by capturing and reproducing human motion on robot in rate of 20Hz with340us computation cost for each process.